Self-harm in people with epilepsy: a retrospective cohort study. - Meyer, N; Voysey, M; Holmes, J; Casey, D; Hawton, K (Blackwell Publishing Inc., 2014)
OBJECTIVES: Little is known about self-harm in people with epilepsy, despite suicide being recognized as a leading cause of mortality in this population. This study aimed to investigate the characteristics of self-harm in people with epilepsy, and associated demographic and psychosocial factors. METHODS: Patients presenting to hospital following self-harm between 1994 and 2008 were identified from the Oxford Monitoring System for Self-Harm. Epilepsy diagnosis was confirmed through review of medical records. Demographic features, patient, and self-harm characteristics of 132 people with epilepsy and 9,778 self-harm patients without epilepsy were compared using a regression model, adjusting for age, sex, and repetition. Patients presenting between 1998 and 2008 were followed up for all-cause mortality to the end of 2011. RESULTS: The rate of self-harm per individual with epilepsy was 2.04 (95% confidence interval [CI] 1.85-2.25) times that of the comparison group, and time between first and second self-harm events was shorter (hazard ratio 1.86; 1.46-2.38). People with epilepsy were significantly more likely to use antiepileptic medication in overdose, although overall methods of self-harm were similar in the two groups. No significant differences in suicide intent scores or the proportion of patients who died by suicide were found. Previous outpatient psychiatric treatment, longer duration of unemployment, experience of violence, and housing problems were associated with self-harm in people with epilepsy. SIGNIFICANCE: People with epilepsy who self-harm do so more frequently than other self-harm patients. Clinicians should be aware of this and pay attention to contributory factors as these may enhance risk in this population. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.